Enhancing productivity, nutrition, and climate resilience through integrated aquaculture-agriculture systems - Ali, Hazrat; Khondker, Murshed-E-Jahan (WorldFish, 2024)
Malnutrition persists in many regions despite advances in agriculture, highlighting the need for nutrition-sensitive agriculture (NSA) programs that address its root causes. Integrated aquaculture–agriculture (IAA), a key NSA approach, involves cultivating aquatic and terrestrial foods on the same plot, promoting crop diversification for improved nutrition and resilience. This study evaluates the productivity, economic viability, and nutritional output of IAA systems across seven districts in southern Bangladesh, based on a survey of 721 farmers conducted between December 2020 and January 2021. Results demonstrate that IAA enhances farm resilience by diversifying income and food sources, mitigating drought impacts through efficient water use, and reducing reliance on synthetic inputs via nutrient-rich pond sediment. Specific IAA combinations improve both nutritional and economic outcomes, offering a sustainable pathway to address malnutrition and climate challenges.